PROPHYLACTIC ANTIBIOTICS IN CAESAREAN DELIVERIES IN A TERITIARY CARE TEACHING HOSPITAL - GADDE, RAJASREE; GOGINENI, SAJANA; SRI, KANCHARLA CHANDANA; INDRAJA, JIRRA; BRAHMI, MARADANI; GHANTA, VIJAYA KUMAR; KANAGALA, VISWA SRUJANI (International Journal of Current Pharmaceutical Research, 2021)
Objective: Prophylactic antibiotics are used to prevent post-operative infections after Caesarean Section. Studies have suggested a significant role in the timing of prophylaxis. The aim of the study was to evaluate the pattern of antibiotics used and to identify the frequency of post-operative infections in patients undergoing Caesarean Section. Methods: A prospective observational study was carried out for 6 mo. A total of 120 patients who met the inclusion criteria were recruited into the study. Data collection form was prepared using NICE guidelines. A total of 120 medical records were analysed. Results: The results revealed that out of 120 study subjects, prophylactic antibiotics Cefotaxime, Metronidazole and Cefixime were used in 119 (99.17%). Conclusion: This study concludes that giving prophylactic antibiotics before skin incision reduces risk of post-operative infections in women undergoing Caesarean Section. As the patients did not produce any infections post-surgery 3rd generation Cephalosporins along with Nitro-imidazoles can be considered as an effective prophylactic therapy for use during caesarean sections.